A flexible hydrogel tactile sensor with low compressive modulus and dynamic piezoresistive response regulated by lignocellulose/graphene aerogels. Issue 37 (27th August 2021) - Zhou, Hang; Zheng, Li; Meng, Qingyu; Tang, Ruixin; Wang, Zhaosong; Dang, Baokang; Shen, Xiaoping; Sun, Qingfeng
Abstract : Composite elastic polyion hydrogels (EPIHs) were regulated by a lignocellulose/graphene aerogel for pressure sensing featuring the loosening of polyion chains, introduction of porous channels, and reduction of compressive modulus of the system. Abstract : Elastic polyion hydrogels (EPIHs) as pressure sensors require to be microstructurally modified or micropatterned to improve the sensitivity of the parallel-plate sensing configurations. In this work, we designed a novel lignocellulose/EPIH composite microstructure that featured three unique characteristics including the loosening of the polyion chains, the introduction of complex porous channels and the reduction of the compressive modulus of the system for the purpose of piezoresistive sensitivity improvement. This lignocellulose/EPIH displayed hierarchical porous networks involving huger stiffer pores in lignocellulose (hindering the excessive intertwining of polyanion chains) and resultant smaller softer pores in polyanions, leading to high compressibility (80% strain), a high energy dissipation ratio (65%), and low Young's modulus (10 4 KPa) below 40% strain. Ultimately, the hybrid hydrogel possessed an increased conductivity change rate when compressing at low pressures ( C 20 / C 0 = 1.24) because of the soft, porous structure and the introduction of rGO nanosheets as ion repositories. Using this material, a soft tactile sensor with high sensitivity (9.71 MPa −1 within 22 KPa) was demonstrated to reconstruct and simulate the waves of a series of force signals, showing promising applications in the fields of recreation and sports for human–machine interfaces with relatively broad force ranges.